Overview of The Ethnobotany on The Use of Plants as Potential Botanical Pesticides in Indonesia - Whisnu Febry Afrianto; Rivandi Pranandita Putra; Yasri Syarifatul Aini (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Ethnobotany of Indonesian communities utilizes plants as botanical pesticides. Recently, there has been no comprehensive data and information related to the ethnobotany of plants as potential botanical pesticides on a nationwide scale. This paper aimed to depict an overview of ethnobotany as botanical pesticides in Indonesia. The comprehensive literature was collected from the 29 published articles and theses (doctoral, master's, and bachelor's degrees) in English and Bahasa Indonesia. After the data was validated, only 27 papers were related to the study topic. Most literature data is from the western part of Indonesia (Oriental Realm): Java (n=10); followed by Kalimantan (n=7), and Sumatra (n=4). The results showed that 149 plant species were used as botanical pesticides. It consists of 130 species as an insecticide, 12 as a fungicide, 8 as a bactericide, 8 as a molluscicide, 3 as a rodenticide, and 2 as a nematicide. These species were dominated by the Compositae family (14 species) and plant parts used from leaf parts (38.9%). However, 11 species have two to four functions: Archidendron pauciflorum, Areca catechu, Artocarpus heterophyllus, Caryota mitis, Cerbera manghas, Jatropha curcas, Melia azedarach, Morinda citrifolia, Pangium edule, Piper betle, and Piper ningrum. The data of ethnobotany can be used as database information for further research regarding the bioprospecting, formulation, efficacy, and conservation for sustainable use. Furthermore, the development of botanical pesticides is also an alternative to reduce synthetic/chemical pesticides to provide sustainable agriculture.